GIANT URTICARIA IN PRESCHOOL ASSOCIATED WITH ASCARIASIS - Martins da Fonseca, Juliana Salvini Barbosa (2014)
Urticaria is a skin condition characterized by lesions of papules and / or erythematous and edematous plaques fleeting, that persist for minutes or hours, and which appear and disappear in different locations of tegument.Intense itching it´s usually associated. We report the case of a girl preschool, 2 years and 10 months, who presented erythematous, pruritic lesions on the extensive right hemifacial, forearms, chest and abdomen after ingestion of coconut shells and juicebox. The diagnosis was established only after the evidence of elimination of Ascaris lumbricoides through the mouth and anus was then treated with albendazole with complete resolution.